ANALYSIS OF SHALLOT PRICE VOLATILITY AND ITS EFFECT ON VOLATILE FOOD INFLATION IN PAGAR ALAM CITY - Serly Novita Sari; Yulian Junaidi; Trissa Silvian; Muhammad Andri Zuliansyah (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Shallots are one of the strategic horticultural commodities that contribute to volatile food inflation due to their relatively high price fluctuations. This study aims to analyze the volatility of consumer-level shallot prices and their effect on volatile food inflation in Pagar Alam City, South Sumatra Province. The study employs secondary time-series data from 2019–2024, including shallot prices, shallot production, volatile food inflation, and rainfall. Data were obtained from the National Strategic Food Price Information Center (PIHPS), Statistics Indonesia (BPS), Bank Indonesia, the South Sumatra Meteorology, Climatology, and Geophysics Agency (BMKG), and the Trade Office of Pagar Alam City. Data were analyzed using the ARCH/GARCH model to measure price volatility and multiple linear regression to examine the effect of shallot prices on volatile food inflation. Prior to estimation, the data were tested for stationarity using the Augmented Dickey-Fuller (ADF) test. The results indicate that shallot prices in Pagar Alam City exhibit high and persistent volatility, particularly during periods of heavy rainfall and food distribution disruptions. Regression results show that shallot prices have a positive and significant effect on volatile food inflation, while increased shallot production tends to reduce food inflation. Thus, shallot price volatility is one of the factors contributing to volatile food inflation in Pagar Alam City. The ARCH/GARCH model can serve as a useful tool for price monitoring and the formulation of regional food price stabilization policies. Keywords: Inflation, rice volatility; shallots; volatile food.